Transforming Evidence-Based Radiography : A Longitudinal Phenomenographic Study of Conceptual Change and Clinical Implementation - Blom, Johannes; Andersson, Camilla; Fridell, Kent (Journal of Radiology Nursing, 2026)
Background: Evidence-based radiography (EBR) is one of the cornerstones of modern Radiography. The integration of EBR into clinical practice remains challenging, and radiology nurses (RNs) often face barriers due to time constraints, production demands, and limited research tradition within their professions. Objective: The objective was to explore how experienced RNs conceptualize EBR before, during, and after a university-level course of evidence-based quality improvement and identify key barriers to clinical implementation. Method: With a longitudinal qualitative phenomenographic approach, semi-structured interviews were conducted at three time points with five clinically experienced participants enrolled in an EBR course. The course included one theoretical modality and one quality improvement project modality at the clinical setting of the students. Interviews focused on the conceptual understanding of EBR and the practical application in clinical practice. Results: Participants’ understanding of EBR evolved from a narrow, research-focused concept to a broader understanding of EBR as a practical tool for quality improvement in daily practice. While the course enhanced conceptual understanding and engagement, implementation of EBR was hampered by organizational challenges. Managerial support was as a key factor for success. Conclusions: A structured course of evidence-based quality improvement can foster a deeper understanding and motivation among RNs. However, successful implementation requires organizational commitment, leadership involvement, and dedicated time within the clinical workflows, underscoring that EBR is not optional but mandated for high-quality health care.
Keywords: Clinical implementation; Evidence-based radiography; Leadership in health care; Phenomenography; Professional education; Quality improvement; Radiology nursing